PTH-321 Exosomes and microparticles: distinct extracellular compartments which convey genetic information in the colorectal tumour microenvironment. (22nd June 2015) - Bhome, R; Goh, R; Primrose, J; Sayan, AE; Mirnezami, A
Abstract : Introduction: Exosomes and microparticles (MPs) are extracellular vesicles secreted by tumour and stromal cells. Exosomes (40–100 nm) originate in the cytoplasm and are a product of the lysosome-endosome pathway. MPs (100–1000 nm) are larger vesicles which simply bud off from the cell membrane. Exosomes and MPs are known to contain oncogenic (e.g. microRNA-21) and tumour suppressing (e.g. microRNA-200b) microRNAs (miRs). We aim to: (i) screen for cancer-associated microRNAs which are upregulated in exosomes/ MPs from human colorectal cancer fibroblasts; (ii) ascertain the effect of myofibroblast transdifferentiation on cellular and vesicular miR-21 content; (iii) ascertain the effect of epithelial-mesenchymal transition (EMT) on cellular and vesicular miR-200b content; and (iv) compare cellular, exosomal and MP microRNA content for each model above. Method: Several models were used: (i) primary cancer-associated and normal human colorectal fibroblasts; (ii) HFFF2 fibroblasts – treated with TGF-beta (myofibroblasts) and untreated (fibroblasts); and (iii) SIP-1 induced (EMT positive) and uninduced (EMT negative) DLD-1 colorectal cancer cells. Exosomes and MPs were isolated by selective centrifugation and validated by transmission electron microscopy, western blotting and flow cytometry. A cancer microRNA array (Quantimir) was used to screen for 95 specific microRNAs. Quantitative PCR (TaqMan) was used to measure relative miR-21 and miR-200b concentrations. Results: Screening revealed distinct microRNA expression profiles in cancer-associated and normal colorectal fibroblasts. MiR-149 and -150 were upregulated in the cellular compartment, miR-92 and -133 in the MP compartment and miR-17–3p and -202 in the exosomal compartment of cancer-associated fibroblasts. Cellular miR-21 concentration was exponentially higher in myofibroblasts than fibroblasts. This was reflected at the exosomal (2.28+/-0.03 vs. 1.00+/-0.04) but not the MP level. SIP induced colorectal cancer cells had 13-fold less miR-200b than uninduced cells. Again, this was reflected at the exosomal (0.24+/-0.01 vs. 1.00+/-0.04) but not the MP level. Conclusion: MicroRNA screening showed that the cellular, exosomal and MP compartments contain distinct microRNA profiles. In the myofibroblast transdifferentiation and EMT models, exosomal but not MP microRNA concentrations changed significantly and mirrored that of the parent cells. Compared to MPs, exosomes originate deep within the cytoplasm and their proximity to the nuclear machinery may explain this phenomenon. Disclosure of interest: None Declared.